2022
DOI: 10.1002/etc.5415
|View full text |Cite
|
Sign up to set email alerts
|

Investigations On the Fish Acute Toxicity of Fragrance Ingredients Involving Chinese Fish Species and Zebrafish Embryos

Abstract: While zebrafish (Danio rerio) have been accepted worldwide for evaluating chemical hazards to aquatic vertebrates, and in some countries it is mandated to generate fish toxicity data using native species, such as Chinese rare minnow (Gobiocypris rarus) in China. This represents an additional regulatory constraint that may cause redundant tests, additional animal uses, and higher costs. Previous studies showed that juvenile G. rarus was more sensitive than zebrafish juveniles and embryos to metals. To better un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…With the restriction of using vertebrates in toxicity tests, zebrafish embryos have become a promising alternative for fish bioaccumulation and toxicity tests because many studies found similar sensitivity to diverse chemicals across embryo and later fish life stages, 69 though age specific exceptions have also been reported. 49 Herein, we systematically examined the toxicokinetic processes of eight pharmaceuticals with diverse physicochemical properties and pharmacokinetic attributes using zebrafish embryos as a model aquatic species, and then applied the human pharmacokinetic parameter V D to develop predictive fish bioconcentration models.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…With the restriction of using vertebrates in toxicity tests, zebrafish embryos have become a promising alternative for fish bioaccumulation and toxicity tests because many studies found similar sensitivity to diverse chemicals across embryo and later fish life stages, 69 though age specific exceptions have also been reported. 49 Herein, we systematically examined the toxicokinetic processes of eight pharmaceuticals with diverse physicochemical properties and pharmacokinetic attributes using zebrafish embryos as a model aquatic species, and then applied the human pharmacokinetic parameter V D to develop predictive fish bioconcentration models.…”
Section: ■ Results and Discussionmentioning
confidence: 99%